Études mMesopotamiennes = Mesopotamian studies. - Déroche, Vincent,; Masetti-Rouault, Maria Grazia,; Nicolle, Christophe, (Archaeopress Publishing Ltd, 2018)
This volume presents a collection of articles, communications and preliminary reports representing the advancement, in recent years, of human sciences - archaeological, historical, philological and cultural researches - concerning ancient Mesopotamia area studies.